Kajian Pemikiran Paulo Freire: Penerapan Pendidikan Hadap Masalah Dalam Pendidikan Kewargangeraan di Indonesia - Nurlatifa, Nurlatifa; Zai, Ronaldo; Samsuri, Samsuri; Suyato, Suyato (Jurnal Ilmiah Mandala Education (JIME), 2023)
Paulo Freire's Thoughts on Problem-posing education were born from his criticism of bank-style education that made learners as savings where knowledge was filled without any interaction between teachers and learners. In Problem-posing education, students are directed to learn directly from the problems around them. Freire's Facing Problems Education aims to foster critical awareness possessed by students to examine problems that occur in the social, economic, political, and cultural fields. Civic education, as one of the subjects that aim to form good citizens, needs to apply the concept of facing problems in the learning process of civic education. This is because civic education has material related to citizens' lives. The application of Problem-posing education in civic education aims to enable students who are part of citizens to have critical thinking and awareness in examining problems that occur amid national and state life.